2009
DOI: 10.1038/jid.2008.203
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Gene Expression Studies in Congenital Melanocytic Nevi: Insight into Initial Steps of Melanotumorigenesis

Abstract: Large congenital melanocytic nevi (CMNs) are said to have a higher propensity to malignant transformation compared with acquired nevi. Thus, they represent a good model for studying initial steps of melanotumorigenesis. We have performed genotypic (karyotype, fluorescence in situ hybridization, and mutational analyses) and differential expression studies on a large cohort of medium (n=3) and large (n=24) CMN. Chromosomal abnormalities were rare and single, a feature probably reflecting the benignity of these l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 40 publications
6
53
0
1
Order By: Relevance
“…The frequency of NRAS mutations in medium-sized congenital nevi is 64-70% [39][40][41] and raises to 94.7% in large-giant congenital nevi where it has been recently recognized as the sole recurrent somatic mutation [42]. It has been suggested that NRAS mutations exert stronger growth signals, resulting in the formation of larger nevi than those linked to BRAF mutations [43].…”
Section: Nras In Melanocytic Cell Neoplasmsmentioning
confidence: 99%
“…The frequency of NRAS mutations in medium-sized congenital nevi is 64-70% [39][40][41] and raises to 94.7% in large-giant congenital nevi where it has been recently recognized as the sole recurrent somatic mutation [42]. It has been suggested that NRAS mutations exert stronger growth signals, resulting in the formation of larger nevi than those linked to BRAF mutations [43].…”
Section: Nras In Melanocytic Cell Neoplasmsmentioning
confidence: 99%
“…Next generation DNA sequencing methods indicate that the cellular DNA repair machinery is unable to keep up with the background rate of errors that accumulate in the genomes of cells of multicellular organisms, most of which are likely to prove biologically inconsequential (4,(7)(8)(9)(10)(11)(12). In addition, there is growing evidence of changes in the molecular mechanisms that regulate stem cell differentiation and its control during normal development and aging, as well as in response to wounding, infections, and other perturbations of normal physiology (13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of DiRas3 appeared strongly increased in endometriosis epithelial cells as compared to normal ovarian epithelial cells [49]. Furthermore, the expression of the DiRas3 gene was up-regulated in the keratinocytes from the large congenital melanocytic nevi bearing the activating B-RAF-V600E mutation [50]. 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 12 There is an increasing number of genes that originally have been assigned a tumour suppressor or an oncogenic role, but after further investigations appeared to have a dual function depending on cellular context.…”
Section: Discussionmentioning
confidence: 93%